Parental Socialization Effort and the Intergenerational Transmission of Risk Preferences - Sule Alan; Nazli Baydar; Teodora Boneva; Thomas F. Crossley; Seda Ertac (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
We study the transmission of risk attitudes in a unique survey of mothers and children in which both participated in an incentivized risk preference elicitation task. We document that risk preferences are correlated between mothers and children when the children are just 7 to 8 years old. This correlation is only present for daughters. We show that a measure of parental involvement is a strong moderator of the association between mothers' and daughters' risk tolerance. These findings support a role for socialization in the intergenerational transmission of preferences that predict economic behaviour.
Keywords: C93; J16; D03; 330; risk preferences; intergenerational transmission; children's economic decisions; field experiments; Kinder; Risikopräferenz; Generationengerechtigkeit; Sozialisation; Eltern; Test